Increasing interest in writing and ability to write explanatory texts through project-based learning models in students - Afrizal, Eri; Syamsi, Kastam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to increase interest in writing explanatory texts through a project-based learning model in class XIC students of SMA Negeri 1 Bunyu and improve the ability to write explanatory texts through a project-based learning model in students of class XIC of SMA Negeri 1 Bunyu. The research conducted is a Classroom Action Research (PTK) developed by Kemmis and Taggart. The research design consists of four stages, namely: (a) planning, (b) action, (c) observation, and (d) reflection. The subject of the study was 31 students of class XIC of SMA Negeri 1 Bunyu. The research was carried out in two cycles, each cycle consisted of two meetings. Data collection uses observation sheets, interview guidelines, questionnaires, learning outcome tests, activity documentation, and field notes. Data analysis techniques include the process of classroom actions carried out qualitatively and the results of action analysis in the form of scores and scores quantitatively. The results of this study concluded that after learning using a project-based learning model, students' interest in writing and ability to write explanatory texts increased. The increase in students' interest in writing, the average initial condition was 53.03, which was in the low category. In the first cycle, it increased to 76.22, in the medium category. In the second cycle, it increased to 104.42, which is in the high category. The improvement of students' ability to write explanatory texts from the initial condition averaged 49.52, increased in the first cycle to 71.19 and in the second cycle to 83.39. It is proven that the Project-Based Learning Model is able to increase students' interest in writing and ability to write explanatory texts.